A randomized controlled trial of brain training with non-action video games in older adults: results of the 3-month follow-up - Ballesteros, Soledad; Mayas, Julia; Prieto, Antonio; Toril, Pilar; Pita, Carmen; Laura, Ponce de León; Reales, José M.; Waterworth, John A. (Frontiers in Aging Neuroscience, 2015)
This randomized controlled study (ClinicalTrials.gov NCT02007616) investigated the maintenance of training effects of 20 1-hr non-action video game training sessions with selected games from a commercial package on several age-declining cognitive functions and subjective wellbeing after a 3-month no-contact period. Two groups of cognitively normal older adults participated in both the post-training (posttest) and the present follow-up study, the experimental group who received training and the control group who attended several meetings with the research team during the study but did not receive training. Groups were similar at baseline on demographics, vocabulary, global cognition, and depression status. Significant improvements in the trained group, and no variation in the control group had been previously found at posttest, in processing speed, attention and visual recognition memory, as well as in two dimensions of subjective wellbeing. In the current study, improvement from baseline to 3 months follow-up was found only in wellbeing (Affection and Assertivity dimensions) in the trained group whereas there was no change in the control group. Previous significant improvements in processing speed, attention and spatial memory become nonsignificant after the 3-month interval. Training older adults with non-action video games enhanced aspects of cognition just after training but this effect disappeared after a 3-month no-contact follow-up period. Cognitive plasticity can be induced in older adults by training, but to maintain the benefits periodic boosting sessions would be necessary.